Desain Perkerasan Jalan Sumberboto - Gununggede Blitar Menggunakan Metode Manual Desain - Uminarsih Uminarsih; Yosef Cahyo Setianto Poernomo; Agata Iwan Candra; Fajar Romadhon (Jurnal Manajemen Teknologi & Teknik Sipil, 2021)
The road is an access that connects an area with other areas. With the road, mobility will be easier so that it has an impact on increasing or stabilizing the economy. The Sumberboto-Gunung Gede Blitar road section is one of the access roads to Tambakrejo beach tourism. To improve comfort and safety for road users, it is necessary to improve road quality. This study aims to plan the pavement on the Sumberboto-Gunung Gede Blitar road section. The planning is carried out on the condition of the heavily damaged pavement, with a service life of more than 10 years, the width of the road is 4 meters, the length of the road is 6 kilometers, the type of collector road is class II, and the type of pavement is laston. The planning carried out includes the addition of roads in the hills of Blitar Regency, the data used includes the condition of the sections on the road with calculations referring to the Design Manual Number 02/M/BM/2013 road pavement. The planning results obtained road construction with flexible pavement, with a specification of a surface layer of 10 cm, a layer of 20 cm for the top foundation, 25 cm for the bottom layer of the foundation. From this plan, a total budget of Rp. 13,572,808,084.00 (thirteen billion five hundred seventy-two million eight hundred thousand rupiah) is required. With these results, it can be used as a reference in realizing road construction on the Sumberboto-Gunung Gede Blitar road section.